Evaluation of the Implementation of Function-Based Responsibility Accounting - Sari, Anjela Yuliantika Kumala; Parju, Parju; Wibowo, Agung; Muchayatin, Muchayatin (Untag Business and Accounting Review, 2024)
Implementation of Function-Based Responsibility Accounting is a system used to determine the level of responsibility carried out by managers and employees in controlling production costs. This study aims to determine the implementation of function-based responsibility accounting for determining burdens, measuring performance, evaluating, and knowing the awards given by the company to employees. This study is located at PT.TIMW Bawen Unggaran. The method used in this study is descriptive qualitative by collecting data through interviews with managers and heads of production along with documentation of related documents. The analysis techniques used are data reduction, data presentation, and conclusion. The results obtained that the implementation of function-based responsibility accounting at PT.TIMW in determining burdens, measuring performance, evaluating and awards is good, but needs to be improved so that its performance is optimal.